Avaliação da iluminação para ambientes educacionais visando eficiência energética: estudo de caso da edificação do Centro de Energias Alternativas e Renováveis (CEAR/UFPB) - Santana, Camila Sales Nóbrega de (2018)
On the stage of development and support of the model adopted in the present day, the built environment has demanded a great amount of energy and materials consumption strong. Such a situation can generate, in extreme situations, environmental imbalances and deterioration in the quality of life of the people, especially in developing countries. In order to check the availability of natural lighting and impacts in the design of artificial lighting, which can lead to excessive power consumption, this study evaluated this performance with a focus on autonomy of natural lighting in meeting rooms block classes of alternative and renewable energy Center-DINE, located at the Federal University of Paraíba, João Pessoa – Paraíba. The study consisted in the analysis during the cycle of a year, June to March 2017 2018, integrated scenarios: (i) characterization and formal composition of building bioclimatic, (ii) gauging levels of natural lighting on the equinoxes and solstices correlating them with the amount of recommended illuminance by NBR 15:215-4:2005 for teaching environments, (iii) computer simulation in Shetchup programs and Dialux of the equinoxes and solstices and (iv) General review of the energy consumption with respect to cost/benefit ratio of the amount of artificial lighting needed inside the classrooms. The results indicate that the autonomy of natural light was high during most of the day, but it was insufficient to meet the recommendations requested within the classrooms. In this way, the present study proposed to appropriate alternative strategies (bioclimatic and artificial) for technical feasibility and energy efficiency. As a result of the proposed intervention, the impact on energy consumption was sufficient to ensure operational viability in classrooms, as well as a reduction of about 62.68% of the total of the artificial lighting and 38% de CO 2-eq/ year consumed on the spot per month.